SERUM LACTATE - PREDICTIVE FACTOR IN SEPTIC SHOCK IN INFANTS AND CHILDREN - Antonio Andrusca; Cristina Maria Mihai; Adriana Luminita Balasa; Larisia Mihai; Simona Claudia Cambrea; Irina Ion; Corina Elena Frecus; Tatiana Chisnoiu; Alexandru Cosmin Pantazi; Constantin Ionescu; Ancuta Lupu; Ileana Ioniuc; et al. (Romanian Society of Oral Rehabilitation, 2024)
Background: In the pediatric intensive care unit (PICU), sepsis, sepsis syndromes, septic shock, and multiorgan system failure are frequently encountered and are considered important conditions; Methods: This is a retrospective, observational study over a period of 3 years, that is aimed to investigate the predictive role of lactate levels at admission in order to evaluate disease progression of pediatric patients with septic shock syndrome with the role to identify whether lactate levels at admission could serve as a significant predictor of adverse outcomes. The sample consisted of 21 patients between 1 and 36 months, diagnosed and treated for hemodynamic shock in a tertiary center; Results: The study found that lactate level at admission greater than or equal to 4.95 was associated with 32.5 times increased odds of serious evolution. The study also identified other potential predictors, such as lactate level 12 hours after admission, hemodynamic parameters, and demographic factors; Conclusions: These findings suggest that monitoring lactate levels at admission can provide important information to predict mortality and guiding treatment decisions in pediatric patients with shock syndrome.